Republic of Madagascar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper surveys the economic costs of corruption in Madagascar, and provides a few ideas on how to advance anticorruption reforms. Madagascar's governance indicators weakened significantly during the transition period 2009-13. Governance indicators that generally were on par with middle-income countries in Sub-Saharan Africa (SSA) ten years ago have regressed and converged to the average of fragile SSA countries. After the return of constitutional order in 2014, the government has started to address corruption, mainly through the introduction of new laws so far. More emphasis is needed on effective implementation and raising sufficient resources to fight corruption.